Estudio de factibilidad para la creación de un ente de control y regulador de las actividades de las empresas constructoras en la ciudad de Quito - Landeta López, Estefanía Maricela (2014)
In Ecuador the estate sector is considered as the most important in the last years, for his great contribution to the country's economy, therefore the Government provides facilities to Ecuadorian families, so they have access a worthy housing and at the same time, it contributes in the development of this market, attracting a lot of investment to the sector. At this time, the companies are operating in this market, it has taken advantage in the lack of control by Government, and it is harming those who search an own housing. The research was conducted in the metropolitan municipality of Quito, here it was verified that there are cases in which several families have been affected.